2016
DOI: 10.1007/s00394-016-1179-z
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and cardiovascular diseases: critical review of current research

Abstract: Caffeine is a most widely consumed physiological stimulant worldwide, which is consumed via natural sources, such as coffee and tea, and now marketed sources such as energy drinks and other dietary supplements. This wide use has led to concerns regarding the safety of caffeine and its proposed beneficial role in alertness, performance and energy expenditure and side effects in the cardiovascular system. The question remains "Which dose is safe?", as the population does not appear to adhere to the strict guidel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 137 publications
0
48
1
6
Order By: Relevance
“…In animal models of PD, treatment with caffeine ameliorated oxidative stress, restored the depletion of midbrain and striatal dopamine, prevented decline in motor activities and muscular strength, and improved norepinephrine level . All‐cause mortality studies suggest that the inverse association with caffeine may be attributable to caffeine's protection against cardiovascular disease and some cancers . We did not assess specific causes of death among patients because of sample size limitations, but we did control for these comorbidities when assessing all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of PD, treatment with caffeine ameliorated oxidative stress, restored the depletion of midbrain and striatal dopamine, prevented decline in motor activities and muscular strength, and improved norepinephrine level . All‐cause mortality studies suggest that the inverse association with caffeine may be attributable to caffeine's protection against cardiovascular disease and some cancers . We did not assess specific causes of death among patients because of sample size limitations, but we did control for these comorbidities when assessing all‐cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Some safety concerns are related to its caffeine content, a physiological stimulant with side effects that may affect cardiovascular outcomes [1]. However, a recent meta-analysis showed that moderate coffee consumption was inversely associated with CVD risk, with the lowest CVD risk at three to five cups per day, and that heavy coffee consumption was not associated with elevated CVD risk [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the consumption of CAF in higher doses than recommended can lead to the decrements in performance as well as trigger negative effects on the cardiovascular system . Furthermore, chronic use of CAF may led to dependence, tolerance, drug craving, and upon abrupt cessation unpleasant withdrawal symptoms .…”
Section: Introductionmentioning
confidence: 99%